The Association of Changes in Pain Acceptance and Headache-Related Disability. Issue 7 (5th October 2018) - Lillis, Jason; Thomas, J Graham; Lipton, Richard B; Rathier, Lucille; Roth, Julie; Pavlovic, Jelena; O'Leary, Kevin C; Bond, Dale S
Abstract: Background: Migraine accounts for substantial suffering and disability. Previous studies show cross-sectional associations between higher pain acceptance and lower headache-related disability in individuals with migraine, but none has evaluated this association longitudinally during migraine treatment. Purpose: This study evaluated whether changes in pain acceptance were associated with changes in headache-related disability and migraine characteristics in a randomized controlled trial (Women's Health and Migraine) that compared effects of behavioral weight loss (BWL) treatment and migraine education (ME) on headache frequency in women with migraine and overweight/obesity. Methods: This was a post hoc analysis of 110 adult women with comorbid migraine and overweight/obesity who received 16 weeks of either BWL or ME. Linear and nonlinear mixed effects modeling methods were used to test for between-group differences in change in pain acceptance, and also to examine the association between change in pain acceptance and change in headache disability. Results: BWL and ME did not differ on improvement in pain acceptance from baseline across post-treatment and follow-up. Improvement in pain acceptance was associated with reduced headache disability, even when controlling for intervention-related improvements in migraine frequency, headache duration, and pain intensity. Conclusions: This study is the first to show that improvements in pain acceptance following two different treatments are associated with greater reductions in headache-related disability, suggesting a potential new target for intervention development. Clinical Trials information: NCT01197196 Abstract : Adults with migraine headaches who reported being more accepting of their headache pain also reported less headache-related disability.